Territorial organization of the population in the region: influence of natural and geographical conditions ("Journal "U". Economy. Management. Finance.", 2025)
This article examines the territorial organization of the population and the natural and geographical factors influencing it.
Keywords: territorial organization of the population; natural and geographical factors